Molecular Imaging and Non-molecular Imaging of Atherosclerotic Plaque Thrombosis - Guo, Bingchen; Li, Zhaoyue; Tu, Peiyang; Tang, Hao; Tu, Yingfeng (Frontiers in Cardiovascular Medicine, 2021)
Thrombosis in the context of atherosclerosis typically results in life-threatening consequences including acute coronary events and ischemic stroke. As such, early detection and treatment of thrombosis in atherosclerosis patients is essential. Clinical diagnosis of thrombosis in these patients is typically based upon a combination of imaging approaches. However, conventional imaging modalities primarily focus on the assessment of anatomical structure and physiological function, severely constraining their ability to detect early thrombus formation or the processes underlying such pathology. Recently, however, novel molecular and nonmolecular imaging strategies have been developed to more accurately assess thrombus composition and activity at the molecular and cellular levels. These approaches have been leveraged to markedly reduce rates of atherothrombotic events in patients suffering from acute coronary syndrome (ACS) by facilitating simultaneous diagnosis and personalized treatment of thrombosis, these patients while enabling the monitoring of plaque hemorrhage as a means of preventing plaque rupture and associated adverse cardiovascular events. Sustained developments in molecular and nonmolecular imaging technologies have enabled the increasingly specific and sensitive diagnosis of atherothrombosis in clinical settings, making these technologies invaluable to patient health. In the present review, we discuss current progress regarding the molecular and nonmolecular imaging of thrombosis in atherosclerosis patients.